2017
DOI: 10.4103/0973-029x.203760
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted morphometric image analysis of cells of normal oral epithelium and oral squamous cell carcinoma

Abstract: Context:Oral squamous cell carcinoma (OSCC) is a malignant neoplasm of epithelial tissue origin. OSCC is traditionally graded into well, moderate and poorly differentiated. The assessment of cellular and nuclear features is very important in the histological grading of OSCC.Aims:To establish morphometric study as an important prognostic indicator of OSCC.Settings and Design:The present study is undertaken for computer-assisted morphometric evaluation of the following parameters: changes in cell perimeter, nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…These findings correlate with our observation of increase in cellular area in the spinous cell layer compared to superficial cells. [ 17 19 , 20 ] Previous studies found that tissues undergoing malignant transformation typically showed a reduction in cellular area before showing reduction in nuclear area, using semiautomatic image analysis techniques. [ 6 17 ] Shabana et al [ 5 ] studied the shape and size of the cells in basal cell layer of the oral epithelium, and they found a progressive increase in the dimensions of nuclei from normal mucosa through traumatic keratosis, lichen planus, leukoplakia, and risk group to carcinoma, with considerable variations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings correlate with our observation of increase in cellular area in the spinous cell layer compared to superficial cells. [ 17 19 , 20 ] Previous studies found that tissues undergoing malignant transformation typically showed a reduction in cellular area before showing reduction in nuclear area, using semiautomatic image analysis techniques. [ 6 17 ] Shabana et al [ 5 ] studied the shape and size of the cells in basal cell layer of the oral epithelium, and they found a progressive increase in the dimensions of nuclei from normal mucosa through traumatic keratosis, lichen planus, leukoplakia, and risk group to carcinoma, with considerable variations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no correlation was found between the staining intensity of the nuclear area (Avg) and the NP (Avg). Kumar et al analyzed the nuclear morphological features of 30 cases of normal oral mucosa and well to moderately differentiated oral squamous cell carcinoma (SCC) by H&E staining, and found that the nuclear area and the NP of SCC were significantly larger than those of normal squamous epithelium ( 15 ). According to the data of the nuclear morphological analysis of 64 cases of breast cancer, as analyzed by cytologic smear, Kashyap et al classified cellular atypia based on Robinson's grading system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the field of digital image analysis has emerged and aims to support the evaluation and annotation of microscopic images using machine learning algorithms . In particular, the morphometric analysis of cells in histological images has gained interest as it can be used for the automatic detection and classification of cells . Morphometry uses quantitative statistical models to learn about size and shape (e.g.…”
Section: Figurementioning
confidence: 99%